Pin1 plays a key role in the response to treatment and clinical outcome in triple negative breast cancer. (March 2020) - Knowlson, Catherine; Haddock, Paula; Bingham, Victoria; McQuaid, Stephen; Mullan, Paul B.; Buckley, Niamh E.
Background: Triple negative breast cancer (TNBC) is the subset of breast cancer associated with the poorest outcome, and currently lacks targeted treatments. Standard of care (SoC) chemotherapy often consists of DNA damaging chemotherapies ± taxanes, with a range of responses observed. However, we currently lack biomarkers to predict this response and lack alternate treatment options. Methods: Pin1 expression was modulated in vitro and proliferation and treatment response was studied. Pin1 expression was analysed in patient samples and correlated with clinical outcome. Results: In this study, we have shown that the prolyl isomerase, Pin1, which is highly expressed in TNBC, plays a key role in pathogenesis of the disease. Knockdown of Pin1 in TNBC resulted in cell death while the opposite is seen in normal cells. We revealed for the first time that loss of Pin1 leads to increased sensitivity to Taxol but only in the absence of functional BRCA1. Conversely, loss of Pin1 results in decreased sensitivity to DNA-damaging agents independent of BRCA1 status. Analysis of Pin1 gene or IHC-based expression in over 200 TNBC patient samples revealed a novel role for Pin1 as a TNBC-specific biomarker, with high expression associated with improved outcome in the context of SoC chemotherapy. Preliminary data indicated this may be extended to other treatment options (e.g. Cisplatin/Parp Inhibitors) that are gaining traction for the treatment of TNBC. Conclusions: This study highlights the important role played by Pin1 in TNBC and highlights the context-dependent functions in modulating cell growth and response to treatment.